Deciding first-order properties of locally tree-decomposable structures. - Frick, Markus (Journal of the ACM)
We introduce the concept of a class of graphs, or more generally, relational structures, being locally tree-decomposable. There are numerous examples of locally tree-decomposable classes, among them the class of planar graphs and all classes of bounded valence or of bounded tree-width. We also consider a slightly more general concept of a class of structures having bounded local tree-width.We show that for each property φ of structures that is definable in first-order logic and for each locally tree-decomposable class C of structures, there is a linear time algorithm deciding whether a given structure A ∈ C has property φ. For classes C of bounded local tree-width, we show that for every k ≥ 1 there is an algorithm solving the same problem in time O(n1+(1/k)) (where n is the cardinality of the input structure).